Azoliums and Ag(I)‐N‐Heterocyclic Carbene Thioglycosides: Synthesis, Reactivity and Bioactivity. Issue 9 (17th February 2022) - Ryzhakov, Dmytro; Beillard, Audrey; Le Bideau, Franck; Al‐Shuaeeb, Riyadh Ahmed Atto; Alami, Mouad; Bantreil, Xavier; Bonnemoy, Aurore; Gautier, Arnaud; Lamaty, Frédéric; Messaoudi, Samir
Abstract: A versatile protocol for the synthesis of azolium thioglycosides is reported. This protocol is based on a PdG3‐catalyzed Migita cross‐coupling between p ‐di‐iodo azoliums and protected or unprotected β‐1‐thioglucose partners. Moreover, a solvent‐free mechanochemistry approach was developed as a unique access to the corresponding Ag(I)‐N‐heterocyclic carbene thioglycosides. Finally, chemical reactivity and antiproliferative bioactivity were examined with azoliums and Ag(I)‐NHC thioglycosides. This study demonstrates a promising potential of these newly synthesized carbohydrate‐based N ‐heterocyclic derivatives. Abstract : By combining a Pd‐catalyzed Migita cross coupling and mechanosynthesis, a series of azoliums and Ag(I)‐ N ‐heterocyclic carbene thioglycoside complexes were synthesized. This new family of carbohydrate derived NHCs displays promising potential as catalysts as well as bioactive compounds.